Sędziowie szlacheccy i urzędnicy sądowi guberni wileńskiej w latach 1801–1831. Szkic do portretu zbiorowego - Korybut-Marciniak, Maria (1976– ); Kowalik, Jolanta (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
After the establishment of Russian rule over the territories of the former Grand Duchy of Lithuania, efforts were initially made to integrate these areas into the empire while maintaining the existing legal system and preserving noble self-government.A key function of the noble assemblies (sejmiks), which were the institutional bedrock of this system, was the election of officials. Every three years, hundreds of representatives of the privileged estate, including members of the judiciary, were elected by the sejmiks. This article analyses the social background, education, wealth, and careers of officials in the Vilnius Gubernia from 1801 to 1831, revealing the increasing stratification within this group.
p. 263-288
Summary in English.
Keywords: personal forms; Vilnius gubernia; Russian Empire; officials; judiciary